AI-Mediated Digital Formative Assessment, EFL Writing: Validity, Teacher Digital Literacy, Ethical Implications. - Utari, Zeli; Sesmiarni, Zulfani; Syafitri, Widya (Journal of English Language and Education, 2026)
The integration of Artificial Intelligence (AI) in formative assessment practices has transformed how English as a Foreign Language (EFL) writing is taught and evaluated. This study employs a qualitative Systematic Literature Review (SLR) guided by the PRISMA protocol to explore empirical and conceptual studies on AI-mediated digital formative assessment, focusing on three key dimensions: validity, teacher digital literacy, and ethical implications. From an initial pool of 237 studies published between 2018 - 2025, 22 studies met the inclusion criteria. A narrative synthesis revealed that while AI tools enhance feedback immediacy and data-driven decision-making, issues of construct validity, teacher competence in AI-based feedback interpretation, and ethical concerns - such as bias and data privacy - remain unresolved. The review concludes that the effective implementation of AI-mediated assessment requires not only technological readiness but also a deep pedagogical understanding and ethical awareness among teachers.